Consumer complaints about food packaging - Bauer, Anna-Sophia; Dörnyei, Krisztina Rita; Krauter, Victoria (Frontiers in Sustainable Food Systems, 2023)
Today, the public's perception of food packaging is primarily negative. This can be triggered by factors such as the use of (fossil) resources, waste generation and (marine) littering. Accordingly, the (re)design of packaging is focusing in particular on the environmental sustainability (e.g. recyclability). However, it seems that in parallel, consumer experience and satisfaction continue to decline. This is reflected in numerous online complaints about packaging. Against this background, the aim of this study is to analyze these complaints and to identify underlying causes. In addition, the study aims to show the extent to which existing European food and packaging legislation already prevent poor packaging design. For this purpose, over 250 complaints were collected, categorized, and evaluated based on images shared online. The study is based on the disconfirmation of expectations theory and the method used leans on Kozinets Netnography, which is described as ethnography on the Internet. In total, twelve design categories were identified that triggered significant dissatisfaction among consumers. These include food packaging that implies a higher quality or quantity of products through text-based information, design elements such as graphics, certain packaging sizes, windows, and sleeves as well as the seemingly excessive use of packaging material. The subsequent discussion shows that the consumer perspective and the legal framework have many points in common and that stricter compliance with the already existing requirements can avoid dissatisfaction in many cases. As a result, this study provides stakeholders from research, development, and politics with an important basis for significantly increasing the consumer satisfaction along with the ecological (re)design of packaging..